Fostering Democracy and Openness: Internal Organizational Communication within Jamaah Tabligh - Ilham Prisgunanto; Iswahyu Pranawukir (Profetik: Jurnal Komunikasi, 2024)
Islam Jamaah in the context of their practices in society, is often perceived as a group, primarily because most members of society are unaware of their workings. The problem of this research is to prove that Jamaah Tabligh is an organization, not a group. The study aims to find out the internal organization communication the members of Jamaah Tabligh (a religious meeting/congregation) and the patterns of dakwah (missionary endeavor) they apply. The study employs the Goldhaber model of organizational communication with a downward model in relation to leadership, the relationship between superiors and subordinates and the selection of leaders. The study uses the qualitative method. Data is obtained through interviews with seven active members of Jamaah Tabligh. The results of the study reveal that the internal organizational communication of Jamaah Tabligh is a large organization because it has international, national and local headquarters. The organizational communication model is very open and democratic. The leaders try to serve the members of the congregation instead of governing them. The openness of this organizational communication model can be seen in deliberations and has caused Jamaah Tabligh to be favored by lower and middle class people